Predicting Ductile Crack Initiation in Steel Bridge Piers with Unstiffened Box Section under Specific Cyclic Loadings Using Detailed and Simplified Evaluation Methods. Issue 9 (September 2015) - Kang, Lan; Ge, Hanbin
Previous research has confirmed the detailed damage index-based evaluation method (DDIM) to be accurate for ductile crack initiation in steel structures under regular cyclic loading, and demonstrated its application to bridge piers and beam-to-column connections. To facilitate practical implementation of the method, two key issues of its calibration for steel structures under irregular cyclic loading are examined. The first pertains to validate the accuracy of DDIM through 4 cyclic tests under irregular cyclic loading. The second aspect involves the development of modified simplified damage index-based evaluation method (MSDIM) to directly determine ductile crack initiation life by fiber analysis, thus avoiding complex shell analysis, which adds expense and complexity. Accordingly, a modification factor is introduced to account for effects of strain concentration. Simplified fiber analyses that employ the MSDIM are shown to predict fracture with good accuracy across the specimen geometries and loading histories.